Odletová hala - Čepl, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2022)
Bakalářská práce se zabývá návrhem ocelové letištní haly pražského letiště půdorysných rozměrů 70 x 40 metrů a konstrukční výšky 9,6 metru. Hlavním prvkem konstrukce jsou rámové vazby s příhradovým vazníkem ve tvaru charakteristické „vlny“ připojeným k hlavním příhradovým sloupům uprostřed rozpětí haly. Rámové vazby jsou doplněny bočními sloupy z plnostěnných profilů připojených k vazníku kloubem. Kotvení všech sloupů jsou provedena taktéž kloubově. Vzdálenost jednotlivých příčných vazeb je 5 metrů a tuhost celku je zajištěna pomocí ztužidel účinných v tlaku.

Bachelor thesis focuses on the design of a steel Prague airport departure hall with dimensions of 70 x 40 meters and a construction height of 9,6 meters. The main components of the construction are steel frames with truss girders in a characteristic "wave" shape connected to the main truss columns in the center of the hall span. Steel frames are supplemented by side columns made from section steel profiles connected to the main girders by joints. All of the columns are hinge-connected in their anchoring. Each lateral steel frame is 5 meters apart and the overall stiffness is secured by bracings effective in compression.
Departure hall
Keywords: Letištní hala; ocelová konstrukce; rámová konstrukce; příhradový vazník; válcované profily; pravoúhlé duté profily; ztužidla; kotvení sloupů; Airport hall; steel structure; steel frame; truss girder; rolled profiles; Hollow steel sections with square cross-section; bracings; column anchorage